SmartArc-based volumetric modulated arc therapy can improve the middle ear, vestibule and cochlea sparing for locoregionally advanced nasopharyngeal carcinoma: a dosimetric comparison with step-and-shoot intensity-modulated radiotherapy - Gao, J (Br J Radiol, 2015)
OBJECTIVE: Radiation-induced sensorineural hearing loss is a common complication after radiotherapy in patients with nasopharyngeal carcinoma (NPC) that significantly affects their quality of life. The goal of this study was to compare SmartArc-based volumetric modulated arc therapy (VMAT-S) with step-and-shoot intensity-modulated radiation therapy (IMRT) for patients with locoregionally advanced NPC with regard to the sparing effect on middle ear, vestibule and cochlea. METHODS: 20 patients with non-metastatic Stage III or IV NPC were selected to have planning with VMAT-S and IMRT [using Philips Pinnacle Planning System (Philips, Fitchburg, WI) for Varian accelerator] for dosimetric comparison. Mean middle ears, vestibule and cochlea doses for the two planning techniques were compared using a paired t-test. Target coverage and dose homogeneity were evaluated by calculating conformity index (CI) and homogeneity index (HI) values. RESULTS: VMAT-S had significantly improved homogeneity and conformity compared with IMRT. Mean HI of planning target volume of gross tumour volume (PGTV) was better with VMAT-S (1.05 ± 0.02) than IMRT (1.09 ± 0.03) (p < 0.001). Mean CI of PGTV is also better with VMAT-S (0.59 ± 0.12) than IMRT (0.54 ± 0.12) (p < 0.001). Mean doses to the left cochleas were 43.8 ± 3.6 and 47.8 ± 4.0 (p < 0.001) for VMAT-S and IMRT plans, respectively. Mean doses to the right cochleas were 42.7 ± 4.7 and 47.6 ± 5.4 (p < 0.001) for VMAT-S and IMRT plans, respectively. VMAT-S also significantly reduced the mean doses to middle ears (p < 0.001 for both) and vestibule (p < 0.001 for both). CONCLUSION: Our results indicate that VMAT-S provides better sparing of hearing apparatus in locoregionally advanced NPC. ADVANCES IN KNOWLEDGE: VMAT-S can improve the middle ear, vestibule and cochlea sparing in patients with locoregionally advanced NPC.